Leadership - Temen, Başak (My University, 2000)
Until recently the word leadership did not feature very much in management literature. The emphasis was on authority, reporting and formal procedures to be followed. Leadership was seen as something that the military and politicians were engaged in. But today it is different. Books on this subject are being sold in the market, industrialists are hailed as great leaders besides the military and political leaders, leadership subject is being thought even in the MBA programmes. Why has all this happened? · There has been a change in the business environment. When the situation is relatively stable, the need to arouse enthusiasm, to energise people, to persuade them to give up old ideas and working practices is less. Management is usually adequate when things are routine and predictable but when the organisation is in trouble and needs a radical change then leadership is called for. · Case studies of firms which were very successful in a consistent way for many years, shows that success has been achieved with the effective leadership from the top exercised by either the founders or chief executives. · It has been examined that leadership does make a difference to the performance of individuals, groups and organisations. It does so at the individual level by creating commitments not by the use of formal authority alone. Committed people are inspired, enthusiastic, dedicated and energised. Leadership also improves the performance of groups by team-building and collective achievements.
Keywords: İNSAN KAYNAKLARI; LİDERLİK